A Base‐Free Pd‐Precatalyst Mediated Suzuki‐Miyaura and Sonogashira Cross‐Coupling in Deep Eutectic Solvents. Issue 8 (27th February 2020) - Thiyagamurthy, Pandurangan; Khan, Fazlur Rahman Nawaz
Abstract: A volatile organic solvent‐free deep eutectic solvent (DES) was prepared by utilizing 1 : 10 ratio of potassium carbonate (PC) as a hydrogen bond acceptor (HBA) and ethylene glycol (EG) as a hydrogen bond donor (HBD). Subsequently, DES was utilized as a solvent in the Pd‐catalyzed Suzuki‐Miyaura or Sonogashira cross‐coupling reactions of boronic acids or acetylenes respectively with in situ generated 2‐bromobenzo[2, 3][1, 4]oxazepino[7, 6‐b]quinoline, 3 The anhydrous conditions without air exclusion, low catalyst loading, low toxicity, high efficiency, low cost, and bioavailability are the advantages of DES in C−C bond forming reactions. Moreover, a gram‐scale reaction under mild conditions with an excellent yield was productive. The one‐pot reaction of 6‐bromo‐2‐chloroquinoline‐3‐carbaldehyde, 1 through 2‐bromobenzo [2, 3][1, 4]oxazepino [7, 6‐b]quinoline, 3 intermediate, and subsequent Suzuki‐Miyaura or Sonogashira coupling was successfully attempted. Abstract : A volatile organic solvent‐free deep eutectic solvent (DESs) was prepared by utilizing potassium carbonate (PC) as a hydrogen bond acceptor (HBA) and ethylene glycol (EG) as hydrogen bond donor (HBD). Subsequently, deep eutectic solvents were utilized as a solvent in the Pd‐catalysed Suzuki‐Miyaura and Sonogashira cross‐coupling reactions insitu generated 2‐bromobenzo[2, 3][1, 4]oxazepino[7, 6‐b] quinoline, 3 with organo‐boronic acids or acetylenes.